Expression and interactions of the ubiquitin receptor ZNF216 - Strachan, Joanna (2012)
Muscle atrophy is a feature of many chronic diseases and contributes to both morbidity and mortality, emphasising the importance of understanding the molecular pathways involved. Zinc finger protein 216 (ZNF216) is an atrogene, a gene which is up-regulated during and directly mediates skeletal muscle atrophy, and encodes the ubiquitin (Ub) receptor protein ZNF216. Herein it is demonstrated that ZNF216 mRNA levels increase in the extensor digitorum longus (EDL) in a lipopolysaccharide (LPS)-infusion rat model of muscle atrophy, relative to saline control. However, combined administration of low level dexamethasone (Dex) with LPS, although sparing muscles from atrophy, did not blunt ZNF216 expression which parallels previous observations for the atrogenes muscle atrophy F-box protein (MAFbx) and muscle RING-finger 1 (MuRF1). ZNF216 expression levels were further elevated in biceps femoris muscle in rats dosed with the statin drug simvastatin (in which severe muscle damage and atrophy occurs), relative to control rats. The ZNF216 protein’s Ub-binding ability and its reported association with the 26S proteasome indicates it may shuttle proteins targeted for degradation to the proteasome as part of the atrophy programme. We utilised immobilised recombinant ZNF216 protein and its Ub-binding Znf_A20 domain alone to capture Ub-modified proteins from rat skeletal muscle that may represent ZNF216’s substrates. Bound proteins specifically eluted by deubiquitination were identified via liquid chromatography tandem mass spectrometry (LC-MS/MS) and included adenylate kinase 1 (AK1) and actin, both previously proposed as substrates of MuRF1. However, ion scores for all candidates were below the accepted threshold of significance and immunoblotting failed to validate LC-MS/MS data. This approach also revealed an increase in a low molecular weight Ub-positive protein from EDL muscle after 24hrs of LPS infusion. Retrospective analysis revealed this Ub-positive protein was consistently captured in other experiments and confirmed by protein MS and immunoblotting to represent an unmodified and unanchored (i.e. not attached to a substrate) K48-linked Ub dimer. Subsequent capture of the Ub dimer using the Znf_UBP domain of isopeptidase T (isoT), a Ub-binding domain selective for the free C-terminus of Ub, confirmed the dimer was unanchored and also revealed a ladder of longer endogenous unanchored poly-Ub chains. Optimised affinity capture conditions has afforded the first opportunity to purify longer free poly-Ub chains and perform the initial molecular analyses of endogenous unanchored poly-Ub purified from in vivo sources.